a+1=b+2
a=b+1
by using algebra like that, you get:
a = b+1 = c+2 = d+3
also, you know that:
a+1 = a + b + c + d + 5
a = a+b+c+d+4
0 = b + c + d + 4
so put that in terms of a:
0 = a - 1 + a - 2 + a - 3 + 4
0= 3a -6 +4
0= 3a -2
-3a = -2
a = 2/3
a + b + c + d = answer
2/3 + 2/3 -1 +2/3 - 2 +2/3 -3 = answer
4(2/3) -6 =answer
8/3 -6 = answer
answer = -3.333333333333333= -3 and 1/3
I'm pretty sure that's right
2006-12-12 13:15:47
·
answer #1
·
answered by Jack B. Nimble 2
·
0⤊
1⤋
From the given equations, we have the following:
a + 1 = a + b + c + d + 5
means b + c + d + 4 = 0
means b + c + d = -4 (1)
b + 2 = a + b + c + d + 5
means a + c + d + 3 = 0
means a + c + d = -3 (2)
c + 3 = a + b + c + d + 5
means a + b + d + 2 = 0
means a + b + d = -2 (3)
d + 4 = a + b + c + d + 5
means a + b + c + 1 = 0
means a + b + c = -1 (4)
Now, we have the following system of linear equations in four(4)
unknowns expressed as follows:
=> b + c + d = -4 (1)
=> a + c + d = -3 (2)
=> a + b + d = -2 (3)
=> a + b + c = -1 (4)
Using an augmented matrix (in the form [A:b]), each row entry corresponds to the equation we have above and we only Write the coefficients of the unknowns a, b, c and d as follows:
/ 0 1 1 1 : -4 \
| 1 0 1 1 : -3 |
| 1 1 0 1 : -2 |
\ 1 1 1 0 : -1 /.
Note: The first column of the above matrix corresponds to the coefficients of a. Similarly for the second, third and fourth column corresponds to the coefficients of b, c and d, respectively.
By using the Gauss-Jordan reduction method to soluve for the unknowns, we have the following:(our goal is to obtain an augmented matrix of the form [I:b'], where I is an identity matrix)
*by interchanging row 1 (R1) and row 2 (R2):
/ 1 0 1 1 : -3 \
| 0 1 1 1 : -4 |
| 1 1 0 1 : -2 |
\ 1 1 1 0 : -1 /
*by interchanging row 3 (R3) and row 4 (R4):
/ 1 0 1 1 : -3 \
| 0 1 1 1 : -4 |
| 1 1 1 0 : -1 |
\ 1 1 0 1 : -2 /
*-R1 + R3; -R1 + R4:
/ 1 0 1 1 : -3 \
| 0 1 1 1 : -4 |
| 0 1 0 -1 : 2 |
\ 0 1 -1 0 : 1 /
*-R2 + R3; -R2 + R4:
/ 1 0 1 1 : -3 \
| 0 1 1 1 : -4 |
| 0 0 -1 -2 : 6 |
\ 0 0 -2 -1 : 5 /
*-R3; (-1/2)R4:
/ 1 0 1 1 : -3 \
| 0 1 1 1 : -4 |
| 0 0 1 2 : -6 |
\ 0 0 1 1/2 : -5/2/
*-R3 + R1; -R3 + R2 ; -R3 + R4:
/ 1 0 0 -1 : 3 \
| 0 1 0 -1 : 2 |
| 0 0 1 2 : -6 |
\ 0 0 0 -3/2 : 7/2/
*(-2/3)R4:
/ 1 0 0 -1 : 3 \
| 0 1 0 -1 : 2 |
| 0 0 1 2 : -6 |
\ 0 0 0 1 : -7/3/
*-R4 + R1; -R4 + R2; -2R4 + R3;
/ 1 0 0 0 : 2/3\
| 0 1 0 0 : -1/3|
| 0 0 1 0 : -4/3|
\ 0 0 0 1 : -7/3/
Observe that we obtain an identity matrix of order 4 from the augmented matrix above. Moreover, the rightmost column is the value of the unknown a, b, c and d, respectively. That is,
a = 2/3,
b = -1/3,
c = -4/3 and
d = -7/3.
Now, if we plug these values on the given equations, we get the following results
a + 1 = 2/3 + 1 = 5/3
b + 2 = -1/3 + 2 = -1/3 + 6/3 = 5/3
c + 3 = -4/3 + 3 = -4/3 + 9/3 = 5/3
d + 4 = -7/3 + 4 = -7/3 + 12/3 = 5/3 and
a + b + c + d + 5 = 2/3 + (-1/3) + (-4/3) + (-7/3) + 5 = -10/3 + 15/3 = 5/3.
Therefore, a + 1 = b + 2 = c + 3 = d + 4 = a + b + c + d + 5 = 5/3.
2006-12-12 13:43:00
·
answer #2
·
answered by rei24 2
·
0⤊
0⤋
a+b+c+d+5 = a+1
b+c+d+4 = 0
c+3=d+4
c+3-d-4 = 0
b+c+d+4 = c-d-1
b+2d+5 = 0
b+2=d+4
b+2-d-4 = 0
b+2d+5 =b-d-2
3d = -7
d = -7/3
-7/3 + 4 = 5/3
so a = 2/3
b = -1/3
c = -4/3
a+b+c+d = -10/3
2006-12-12 13:13:23
·
answer #3
·
answered by yungr01 3
·
0⤊
0⤋
i'd supply myself my dream living house with a large view, a sparkling vehicle for my husband, and then i'd do some thing like international peace. Then i'd start up giving myself stuff back :)
2016-10-18 05:02:04
·
answer #4
·
answered by ? 4
·
0⤊
0⤋
let say
a + 1 = b + 2 = c + 3 = d + 4 = x
therefore a=x-1, b=x-2...etc
so (x-1)+(x-2)...etc = -5
so 4x - 10 = -5
so x = 5/4
so a = 1/4
b = -3/4
c = -7/4
d = -11/4
2006-12-12 13:04:54
·
answer #5
·
answered by puma 2
·
0⤊
0⤋
a+1=b+2=c+3=d+4=a+b+c+d+5
a=b+1=c+3=d+4=a+b+c+d+5
a=b=c+2=d+4=a+b+c+d+5
a=b=c=d+2=a+b+c+d+5
a=b=c=d=a+b+c+d+3
then a=b=c=d=a+b+c+d=0
2006-12-12 13:05:16
·
answer #6
·
answered by fortman 3
·
0⤊
1⤋